Geomagnetic dipole moment and 10Be production rate intercalibration from authigenic 10Be/9Be for the last 1,3 Ma. - Carcaillet, Julien; Bourlès, Didier; Thouveny, Nicolas (Geochemistry, Geophysics, Geosystems, 2004)
A synthesis of authigenic 10Be/9Be ratio records constructed from sedimentary sequences deposited over the last 300 ka in the North East Atlantic and over the 500-1300 ka BP interval in the West Equatorial Pacific Ocean is compared with proxies of the geomagnetic moment variations over the same time intervals. These proxies consist in : i) relative paleointensity records obtained from the same sediments; ii) a sea floor magnetization record derived from magnetic anomalies; iii) an absolute Virtual Dipole Moment (VDM) record constructed from an updated database of absolute paleointensities. The authigenic 10Be/9Be ratio records document the occurrence of the paleomagnetic events (excursions and reversals) reported for these time intervals by paleomagnetic studies. Reconstructions of 10Be/9Be derived magnetic moment records based on theoretical and empirical relationships between 10Be/9Be ratio and absolute VDM allow establishing 10Be derived VDM records that exhibit the same overall structures as the geomagnetic proxy records.